Marx lecturer: notes on the constitution and teaching of (Critique) of Political Economy - Lopes Almeida Teixeira, Adriano (Revista Economia Ensaios, 2024)
This text begins with the assumption that a critique of Marx's political economy is the product of the multi-faceted insertion given by the theorist in the social life of his time, either by the most well-known and explored route that his theoretical studies were, or by his political practice and his professional performance as a journalist. Therefore, Marx's criticism is the result of the interaction of various factors, among which we intend to highlight a little explored facet of him: his moments as a lecturer, when he tried to systematize his ideas and reach out, through direct teaching, to a restricted group of interested people by sharing the results of his theoretical research. The two best known lectures given by Marx ("Wage Labour and Capital," 1865, and "Value, Price and Profit," 1865) will be analyzed both for their importance within Marx's theoretical trajectory towards the constitution of his critique, and for their fruitfulness of indicating elements to support the teaching of "Critique of Political Economy."